3D‐Printed Curved Metasurface with Multifunctional Wavefronts. Issue 15 (14th May 2020) - Li, Haipeng; Wang, Guang‐Ming; Hu, Guangwei; Cai, Tong; Qiu, Cheng‐Wei; Xu, He‐Xiu
Abstract: Achieving multifunctional wavefront controls on curved platforms, especially in the transmissive case, is of pivotal importance in the emerging technological field of communication and detection systems, yet it poses a great challenge. A strategy to control the versatile transmissive structured wavefront on conformal platform is proposed by curving a 3D printed flexible metasurface (MS), and its efficacy is demonstrated. The conformal metasurface (CMS) is designed to have broadband performance by cascading three super‐thin flexible printed circuit boards and two 3D‐printing substrates. A general theoretical strategy is proposed for the projection of a curved surface onto a referenced plane by judiciously engineering the compensation of the curvature‐induced phase. Next, four individual proof‐of‐concept conformal quarter‐cylindrical devices are experimentally characterized with the functionalities to generate highly directive beams, vortex‐beams carrying orbital angular momentums, and dual‐beam steering with different angular positioning, confirming the effectiveness and robustness of the proposed strategy. Most importantly, it is shown that the aforementioned multiple angle‐multiplexed functionalities can be achieved by a single synthesized full‐cylinder CMS. The findings demonstrate a successful approach to setting up a robust, systematic, multifunctional, and ultracompact MS for complete wavefront control over curved platforms. Abstract : A strategy to control the versatile transmissive structured wavefront on conformal platform is proposed by curving printed flexible metasurfaces. A full‐cylinder conformal meta‐device is devised with four functions of a highly directive beam, vortex beams with topological charges of 1 and 2, and a dual‐beam emission. The findings demonstrate a successful approach to integrate multifunctional wavefront controls over a single curved platform.